2016
DOI: 10.1039/c5cc07042b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Au@UiO-66(NH2) structures by small molecule-assisted nucleation for plasmon-enhanced photocatalytic activity

Abstract: We have provided a small molecule-assisted heterogeneous nucleation of MOF route to successfully synthesize Au@UiO-66(NH2) heterostructures. UiO-66(NH2) with a localized electronic state that was characterized by C-AFM exhibited higher photocatalytic activity in the heterostructures via a plasmonic sensitization process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 23 publications
3
70
0
Order By: Relevance
“…In addition, MOFs, specifically, NH 2 ‐MIL‐101, NH 2 ‐MIL‐125(Ti), Cu‐BTC, NH 2 ‐MIL‐88B(Fe), UiO‐66, and ZIF‐8, have been used as host matrices for anchoring g‐C 3 N 4 to fabricate g‐C 3 N 4 ‐based composites with improved photocatalytic performance, which is due to increased chemical heterogeneity as well as efficient interfacial charge transfer from photoexcited g‐C 3 N 4 to MOFs . For example, UiO‐66‐NH 2 , a Zr‐containing MOF constructed of zirconium‐oxo clusters and aminoterephthalates, has a highly chemically stable, flat surface and, thus, has been used as a popular host matrix for dispersing metal and semiconductor nanoparticles for water splitting . However, to date, the application of UiO‐66‐NH 2 covered with g‐C 3 N 4 to derive ZrO 2 /g‐C 3 N 4 heterostructures for H 2 production by water splitting has not been reported in the literature.…”
Section: Introductionsupporting
confidence: 81%
“…In addition, MOFs, specifically, NH 2 ‐MIL‐101, NH 2 ‐MIL‐125(Ti), Cu‐BTC, NH 2 ‐MIL‐88B(Fe), UiO‐66, and ZIF‐8, have been used as host matrices for anchoring g‐C 3 N 4 to fabricate g‐C 3 N 4 ‐based composites with improved photocatalytic performance, which is due to increased chemical heterogeneity as well as efficient interfacial charge transfer from photoexcited g‐C 3 N 4 to MOFs . For example, UiO‐66‐NH 2 , a Zr‐containing MOF constructed of zirconium‐oxo clusters and aminoterephthalates, has a highly chemically stable, flat surface and, thus, has been used as a popular host matrix for dispersing metal and semiconductor nanoparticles for water splitting . However, to date, the application of UiO‐66‐NH 2 covered with g‐C 3 N 4 to derive ZrO 2 /g‐C 3 N 4 heterostructures for H 2 production by water splitting has not been reported in the literature.…”
Section: Introductionsupporting
confidence: 81%
“…A large number of studies had showed that the loading of noble metals could enhance the photocatalytic activity of MOFs. [133][134][135][136][137][138][139][140][141] UiO-66 and UiO-66-NH 2 produced low hydrogen under ultraviolet light. However, when Pt was supported on their surface, [133] the absorption of light and production of hydrogen were effectively increased ( Figure 7).…”
Section: Loading Metals On the Surface Of Mofsmentioning
confidence: 99%
“…To improve the photocatalytic efficiency, effective measures must be taken to suppress the recombination of photo-generated interceptors in MOFs photocatalysts. [133][134][135][136][137][138][139][140][141] The valence-level regulation achieved by doping of transition metal ions is one of the commonly used methods. So far, Scientists had evaluated the activity of the catalyst mostly based on the photocatalytic oxidation activity and the photocatalytic reduction activity of MOFs.…”
Section: Valence-level Regulation Mechanismmentioning
confidence: 99%
“…This leads to a fast, long lived & proficient charge movement . In Cd containing MOF, MLCT from Cd to [4, 4′‐bpy] 3 [S 2 O 3 ] 2 ligand clarify the charge movement . In the series of mixed‐metal NH 2 –UiO‐66[Zr/Ti], the experimental spectral alterations are well‐suited with an early development of Ti 3+ –O–Zr 4+ and it promote alteration to Ti 4+ –O–Zr 3+ via metal–metal charge transfer, where substituted Ti act as intermediary to enable electron transmission from excited ligand to the [Zr/Ti] 6 O 4 [OH] 4 nodes in mixed NH 2 –UiO‐66[Zr/Ti]…”
Section: Functionalitymentioning
confidence: 99%
“…[114] In Cd containing MOF, MLCT from Cd to [4, 4'-bpy] 3 [S 2 O 3 ] 2 ligand clarify the charge movement. [115] In the series of mixed-metal NH 2 [116]…”
Section: Charge Transfermentioning
confidence: 99%